2014
DOI: 10.1017/s1041610214001720
|View full text |Cite
|
Sign up to set email alerts
|

Medication development for agitation and aggression in Alzheimer disease: review and discussion of recent randomized clinical trial design

Abstract: Background The management of disruptive neuropsychiatric symptom (NPS) such as agitation and aggression (A/A) is a major priority in caring for people with Alzheimer’s disease (AD). Few effective pharmacological or non-pharmacological options are available. Results of randomized clinical trials (RCTs) of drugs for A/A have been disappointing. This may result from the absence of biological efficacy for medications tested in treating A/A. It may also be related to methodological issues such as the choice of outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 85 publications
3
59
0
1
Order By: Relevance
“…A weakness of this analysis is that the measure of sedation was relatively unsophisticated. Although review of the literature did not reveal any similar formal mediator analyses, it has long been observed that psychotropic medication with sedative effects may account for some of the benefit of such medications on agitation (Jacobson 2014; Maher et al 2011; Brodaty et al 2003; Seitz et al 2013; Soto et al 2014; Gallagher & Herrmann 2014; Tariot et al 2011). The current study appears to be the first that has statistically demonstrated that this relationship exists between antidepressants and agitation in patients with dementia.…”
Section: Discussionmentioning
confidence: 97%
“…A weakness of this analysis is that the measure of sedation was relatively unsophisticated. Although review of the literature did not reveal any similar formal mediator analyses, it has long been observed that psychotropic medication with sedative effects may account for some of the benefit of such medications on agitation (Jacobson 2014; Maher et al 2011; Brodaty et al 2003; Seitz et al 2013; Soto et al 2014; Gallagher & Herrmann 2014; Tariot et al 2011). The current study appears to be the first that has statistically demonstrated that this relationship exists between antidepressants and agitation in patients with dementia.…”
Section: Discussionmentioning
confidence: 97%
“…Agitation related to dementia is frequently observed clinically (Cohen-Mansfield, 2013;Ballard et al, 2001;Lyketsos et al, 2000), and various pharmacological interventions have been employed to treat this. These treatments include the use of anxiolytic, antidepressant, antipsychotic and anticonvulsant drugs (Antonsdottir et al, 2015;Cummings et al, 2015;Panza et al, 2015;Soto et al, 2015;Kales et al, 2014;Salzman et al, 2008). The most contentious approach relates to the use of antipsychotic drugs , which have been reported to be of only modest value (Ballard et al, 2009;, and to produce adverse effects (Gitlin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the currently available pharmacological treatments for agitation in dementia are of little value, and the adverse effects of antipsychotic drugs are of considerable concern (Sacchetti et al, 2012;Ma et al, 2014;Ballard, 2006;. Basically, there are no officially approved pharmacotherapies for agitation in dementia, and few if any safe and effective pharmacotherapies (Antonsdottir et al, 2015;Cummings et al, 2015;Panza et al, 2015;Soto et al, 2015;Kales et al, 2014;. Also, non-pharmaceutical approaches have been shown to be of very limited value (Ballard et al, 2016;Steinberg, 2016;Kales et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable progress has been made in the last years with a growing number of randomized controlled trials (RCTs) of drugs for NPS. The majority of recent RCTs focused on A/A (8). The limited benefits reported in some RCTs may be accounted for by the absence of a biological link of the tested molecule to NPS and also by key methodological issues.…”
Section: Introductionmentioning
confidence: 99%
“…A high response on placebo was observed in many trials. Moreover, variable definitions of “clinically significant A/A” were used, but most required at least moderate severity of A/A (8). …”
Section: Introductionmentioning
confidence: 99%